2016
DOI: 10.1007/s00040-016-0500-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water and resource availability on ant feeding preferences: a field experiment on the Mediterranean ant Crematogaster scutellaris

Abstract: The gut microbiome is recognised as playing an integral role in the health and ecology of a wide variety of animal taxa. However, the relationship between social behavioural traits and the microbial community has received little attention. Honey bees are highly social and the workers perform different behavioural tasks in the colony that cause them to be exposed to different local environments. Here we examined whether the gut microbial community composition of worker honey bees is associated with the behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 127 publications
(107 reference statements)
1
21
1
Order By: Relevance
“…This evidence contrasts with the behaviour observed in L. niger, where an opposite trend was described (Beckers et al, 1992a(Beckers et al, , 1992b. The behaviour we observed in L. neglectus could be due to an increase in the excitement of fed ants, given that a feed rich in carbohydrates can stimulate individual activity (Davidson, 1998;Frizzi et al, 2016;Lee Cassill & Tschinkel, 1999), although there is no evidence that sugar ingestion increases ant activity in such a short time frame.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This evidence contrasts with the behaviour observed in L. niger, where an opposite trend was described (Beckers et al, 1992a(Beckers et al, , 1992b. The behaviour we observed in L. neglectus could be due to an increase in the excitement of fed ants, given that a feed rich in carbohydrates can stimulate individual activity (Davidson, 1998;Frizzi et al, 2016;Lee Cassill & Tschinkel, 1999), although there is no evidence that sugar ingestion increases ant activity in such a short time frame.…”
Section: Discussioncontrasting
confidence: 99%
“…All nest holes belonged to the same supercolony, the only one known in the area, and hence the results must be considered with caution. For the experiments, we only considered nest holes enclosed within the forecourt, because they were subjected to the same conditions of temperature, humidity and substrate type, factors that may affect the feeding behaviour of ants, particularly towards liquid food sources (Frizzi, Rispoli, Chelazzi, & Santini, ).…”
Section: Methodsmentioning
confidence: 99%
“…Together these results caused the authors to suggest that large spiders may have switched from consuming water-laden crickets to consuming energy-or nutrient-rich small spiders with added water availability. Similarly, in another study, Frizzi et al [54] found that water supplemented ants subsequently consumed the most of a high-sucrose concentration liquid diet. Thus, with increased environmental water, generalists may tend to consume more energy-or nutrient-rich food sources of lower water content ( Figure 1C).…”
Section: Tradeoffs With Other Constraintsmentioning
confidence: 78%
“…How commonly does animal water balance influence food webs? One would expect animal water balance to be infrequently important in perennial wetlands, given high and consistent water availability (Figure 3; in these locations, lower water content, nutrient-rich food may be preferred, Figure 1C, [54] [37] used relationships between soil moisture and rates of herbivory (by crickets) in a floodplain forest in a semi-arid region of Arizona to predict the frequency of similar observations of water-balance associated herbivory across the continental US (Figure 4). They found that these crickets would be expected to exhibit water-balance-driven herbivory at 49% of all soil moisture measurement stations in the US, including mesic locations, at some point in time.…”
Section: Spatiotemporal Variation In the Frequency Of Water-mediated mentioning
confidence: 99%
“…aggressiveness, Grangier & Lester, 2014), colony size, and survival (Wittman et al, 2018), and their importance is supported by the strong preference for this resource shown by many dominant species (e.g. Grover et al, 2007;Abril et al, 2007;Frizzi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%